Mosaic disease of vanilla (Vanilla planifolia Andrews) - the first report from India - L Geetha, J J Solomon, R Suseela Bhai, Joseph Thomas, S N Potty (Journal of Spices and Aromatic Crops, 2003)
Recent disease surveys revealed the occurrence of a mosaic disease in vanilla. The infected plants showed mosaic symptoms, distortion of leaves, leaf curling etc. which are typical symptoms of viral infection. Negative staining of the leaf sap with potassium phosphotungstic acid, uranyl acetate and ammonium molybdate revealed the presence of flexuous rod shaped viral particles. This is the first report of occurrence of viral disease in vanilla from India.